The script of the Vorauer Alexander. Some remarks - Adele Cipolla (Filologia Germanica)
The Vorau manuscript, the most prominent poetic miscellany of the Early Middle High German period, contains a version of the Alexanderlied (a text also preserved in the Strasbourg and Basel manuscripts). Historical and literary reasons have been provided to ascertain the poem’s birthplace(s), conjecturally placed in Cologne or Trier. The script, however, is hard to classify in grammatical terms and no univocal dialectal identity emerges from the analysis. This paper, based on the first-hand collation of the Vorau manuscript, will test the editions’ efficiency as collectors of linguistic data, and compare dialectological interpretations with scribal features of both the Vorauer and the Straßburger Alexander. Renewed attention will be devoted to the late Caroline hand of the Vorau codex and to its inconsistent readings, atomised regionalisms and impenetrable features, which do not allow a unique unquestionable regional attribution. The scrutiny eventually aims at pointing out the hybrid linguistic character of the whole Vorau poem, evidencing methodical troubles in normalising its spellings.